The Meaning of Roles in The Perspective of Internal Auditors Gorontalo - Ayu Rakhma Wuryandini; Lukman Pakaya; Siti Pratiwi Husain (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2022)
This study intends to explore the meaning roles of internal auditors in fraud management. It employed phenomenology towards six internal auditors as the participants. The results indicate that the roles of internal auditors, as the assurance, consulting, as well as filter agent of the auditee’s information, contribute by diagnosing frauds by Fraud Control Plan. Future researchers can use different methods to explore the meaning of roles in other APIP.